Paraconsistent Artificial Neural Networks and EEG Analysis - Abe, Jair Minoro [UNESP] (2010)
The aim of this paper is to present a study of brain EEG waves through a new ANN based on Paraconsistent Annotated Evidential Logic E tau which is capable of manipulating concepts like impreciseness, inconsistency, and paracompleteness in a nontrivial manner. As application, the Paraconsistent Artificial Neural Network - PANN showed capable of recognizing children with Dyslexia with Kappa index at a rate of 80%.